Formulasi Sediaan Lip Balm Kombinasi Ekstrak Etanol Bunga Kecombrang (Etlingera elatior (Jack) R.M.Sm.) Dan Madu (Mel depuratum) Sebagai Antioksidan Alami - Halid, Nur Hatidjah Awaliyah; Mannassai, Siti Nur Azigha Awaliya; Kasih, Ridia Utami; Putri , Risky Juliansyah; Himaniarwati , Himaniarwati; Mus Ifaya (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Kecombrang flower (Etlingera elatior (Jack) R.M.Sm.) contains flavonoids and anthocyanins that have potential as antioxidants and natural colorants, and honey (Mel depuratum) has humectant, anti-inflammatory, and antioxidant properties. This study aims to formulate, evaluate the physical stability and test the antioxidant activity of lip balm preparations combined with kecombrang flower extract and honey. This type of research is experimental with a formulation design of three variations in the concentration of a combination of ethanol extracts of kecombrang flowers 10%, 15%, 20% and honey as much as 6%. Physical stability test was conducted through cycling test method and storage at room temperature, including organoleptic observation, homogeneity, pH, spreadability, adhesiveness, melting point, and humidity. The antioxidant activity test was carried out using the DPPH method which was measured using the UV-Vis spectrophotometry method and the positive control was vitamin C. The results showed that all lip balm preparations met the physical quality requirements that were stable in storage and cycling tests. F0 has an IC50 value of 95.5 μg/mL in the medium category, F1 (10:6) with an IC50 value of 25.88 μg/mL, F2 (15:6) with an IC50 value of 20.79 μg/mL, and F3 (20:6) with an IC50 value of 17.83 μg/mL. The IC50 results of formulas F1, F2 and F3 are in the very strong category, with moisture reaching 82.5%.The combination of kecombrang flower extract and honey can be effectively formulated into a lip balm with stable physical quality and strong antioxidant activity. Further research can be conducted on pharmacological and toxicity tests of the preparation.